Efeito gastroprotetor do óleo essencial da Lippia gracilis Schauer (verbenaceae) - Martins, Jose Diogo Lima (2017)
Gastric ulcer is a disease that affects a large part of the world population, with a prevalence of 2.4% in the Western population and with annual incidence rates of 0.10% to 0.19%, with a high cure rate, but with a high recurrence rate. The essential oil (OE) of Lippia gracilis Schauer (Verbenaceae) is popularly used in the treatment of various disorders and presents antinociceptive, anti-inflammatory, antioxidant and antimicrobial activities, but its gastroprotective effect has not been studied yet. The animals were treated with OE at doses of 20, 60 and 180 mg/kg). The acute ethanol/HCl induced ulcer model was used to evaluate the gastroprotective effect of OE and to investigate some possible mechanisms involved. The animals were pretreated with yohimbine -adrenergic antagonist), glibenclamide (KATP channel blocker), L-NAME (NO synthesis inhibitor), NEM (sulfhydryl grouping blocker), indomethacin (nonsteroidal anti-inflammatory) And all were treated with OE (180 mg/kg). The pylorus ligature model was used to evaluate the effect of OE on mucus secretion and gastric acidity. And the action of OE on the activity of H +, K +-ATPase evaluated by in vitro assay. We observed that OE dose-dependently prevented lesions caused by ethanol/HCl, with decreased edema and loss of epithelial cells. The gastroprotective effect of OE was partially diminuided by pre-treatments with LNAME, glibenclamide, indomethacin and yohimbine, and total with NEM. In the pylori ligation model OE increased mucus production, it was able to increase the pH of the gastric juice, decrease the volume of secretion and [H +]. OE inhibited the activity of H +, K + -ATPase. These results confirm that Lippia gracilis OE has a gastroprotective effect, decreasing gastric secretion and stimulating protective factors, w -adrenergic receptors, prostaglandins and KATP channels.